ANALISIS PENGARUH PARENTS ORIENTATION, LEARNING OUTCOME, SAFE ENVIRONMENT, DAN GOOD TEACHERS TERHADAP PARENTS’ LOYALTY MELALUI PARENTS’ SATISFACTION PADA ORANGTUA SISWA SD PLUS ARK SIDIKALANG - TAMBUNAN, WANDI PANGIHUTAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
A good education system will create superior human resources, and this makes the country progress. Education is the source of the nation's progress. Students are future assets that will determine the progress of the nation. Teachers have a crucial role in educating them with various competencies and forging student character. Teachers, Students, and Parents must collaborate to advance education. Educational success is not only determined by teachers at school, but also by students and parents. The three stakeholders need to work together to create a healthy and intelligent learning ecosystem. This research is a causal research using quantitative methods and processed with the help of a statistical program, namely SPSS version 22.0. Data collection was carried out by distributing questionnaires to 130 respondents with predetermined respondent characteristics. In this study there were 9 hypotheses of which seven hypotheses were accepted and two hypotheses were rejected. The accepted hypothesis is that parents' orientation has a significant effect on parents' school satisfaction, learning outcomes have a significant effect on parents' school satisfaction, safe environment has a significant effect on parents' school satisfaction, good teachers have a significant effect on parents' school satisfaction, parents' orientation has a significant effect on parents' school loyalty, good teachers have a significant effect on parents' school loyalty, parents' school satisfaction has a significant effect on parents' school loyalty. The rejected hypothesis is that learning outcomes have a significant effect on parents' school loyalty, safe environment has a significant effect on parents' school loyalty. ABSTRAKSistem pendidikan yang baik akan menciptakan sumber daya manusia yang unggul, dan ini membuat negara menjadi maju. Pendidikan merupakan sumber kemajuan bangsa. Siswa merupakan aset masa depan yang kelak menentukan kemajuan bangsa. Guru mempunyai peran krusial dalam mendidik mereka dengan beragam kompetensi dan menempa karakter siswa. Guru, Siswa, dan Orangtua harus berkolaborasi untuk memajukan pendidikan. Sukses pendidikan tak hanya ditentukan oleh guru di sekolah, tetapi juga oleh siswa dan orangtua. Ketiga pemangku kepentingan perlu bekerja sama untuk menciptakan ekosistem pembelajaran yang sehat dan mencerdaskan. Penelitian ini merupakan penelitian yang bersifat kausal dengan menggunakan metode kuantitatif dan diolah dengan bantuan program statistik yaitu SPSS versi 22.0. Pengumpulan data dilakukan dengan penyebaran kuesioner kepada 130 responden dengan karakteristik responden yang telah ditentukan. Dalam penelitian ini terdapat 9 hipotesis diantaranya tujuh hipotesis diterima dan dua hipotesis ditolak. Hipotesis yang diterima adalah parents’ orientation berpengaruh sigifikan terhadap parents’ school satisfaction, learning outcome berpengaruh sigifikan terhadap parents’ school satisfaction, safe environment berpengaruh sigifikan terhadap parents’ school satisfaction, good teachers berpengaruh sigifikan terhadap parents’ school satisfaction, parents’ orientation berpengaruh sigifikan terhadap parents’ school loyalty, good teachers berpengaruh sigifikan terhadap parents’ school loyalty, parents’ school satisfaction berpengaruh sigifikan terhadap parents’ school loyalty. Hipotesis yang ditolak adalah learning outcome berpengaruh sigifikan terhadap parents’ school loyalty, safe environment berpengaruh sigifikan terhadap parents’ school loyalty.